Практичні рекомендації щодо проектування торцевих розподільних систем планетарних гідромашин - Панченко, Анатолій Іванович; Волошина, Анжела Анатоліївна; Холод, Ігор Михайлович; Волошин, А. А.; Panchenko, Anatolii; Voloshina, Anzhela; Kholod, Ihor; Voloshin, А. (Запоріжжя : 2024, 2024)
UA: Основною характеристикою будь-якої розподільної системи є її пропускна здатність (витрата робочої рідини), що визначається площею прохідного перерізу цієї системи. Збільшення площі прохідного перерізу розподільної системи можна досягти шляхом використання додаткових розвантажувальних вікон рухомого розподільника в якості робочих. Встановлено, що додаткове використання розвантажувальних вікон призводить як до збільшення пропускної спроможності розподільної системи, так і до зміни амплітуди коливань (пульсації) потоку робочої рідини. Розроблено схему руху робочої рідини до робочих камер планетарного гідромотора, що дозволяє визначати кутове розташування вікон рухомого розподільника в залежності від його кінематичної схеми. Обґрунтовано максимальну кількість використання додаткових робочих вікон. Розроблено практичні рекомендації щодо кутового зміщення вікон рухомого розподільника та визначення пропускної спроможності розподільної системи залежно від її кінематичної схеми та кількості додаткових робочих вікон. Розроблені практичні рекомендації дозволяють проектувати розподільні системи планетарних гідромашин із заданими вихідними характеристиками. EN: One of the main units determining the stability of the planetary hydraulic machine is its distribution system required to form a rotating hydraulic field. Physical processes occurring in the end system of the planetary hydraulic motor during operation are always associated with the movement of the working fluid through channels with local resistances and the working fluid distribution system. The main characteristic of the distribution system is its throughput (flow rate of the working fluid), which is determined by the cross-sectional area of this system, which depends on the use of the unloading windows of the movable distributor as working ones. The use of unloading windows as additional working ones allows to increase the throughput of the distribution system, and their specific angular location allows to ensure the constancy of the output characteristics of the planetary hydraulic motor. Therefore, improving the output characteristics of the planetary hydraulic motor by developing practical recommendations for the angular location (shift) of the working windows when designing its distribution systems is an urgent scientific problem. It has been established that the additional use of unloading windows leads to both an increase in the throughput of the distribution system and a change in the pulsation of the working fluid flow. A scheme of fluid movement to the working chambers of the hydraulic motor has been developed, allowing to determine the angular arrangement of the windows of the movable distributor depending on its kinematic scheme. The maximum number of additional working windows has been substantiated. Practical recommendations have been developed for the angular displacement of the windows of the movable distributor and determining the capacity of the distribution system depending on its kinematic scheme and the number of additional working windows. The developed practical recommendations allow to design distribution systems of planetary hydraulic machines with specified output characteristics.
Practical recommendations for designing end distribution systems of planetary hydromachines
Keywords: рухомий розподільник; нерухомий розподільник; кінематична схема; робочі вікна; розвантажувальні вікна; робоча рідина; проточні частини; movable distributor; fixed distributor; kinematic diagram; working windows; unloading windows; working fluid; flow parts